Image adaptive selective encryption of vector quantization index compression - Hasan, Y.; Ahmed, M.F.A.; Abdelhamid, T.K. (2009 16th IEEE International Conference on Image Processing (ICIP), 2009)
The foremost issues with most of the existing selective encryption (SE) schemes of images are vulnerability to cryptographic and application specific attacks, reduction in the compression performance, insubstantial computational savings relative to full encryption, and lack of bit stream compliance. This paper is the first one that proposes effective schemes for joint vector quantization (VQ) based image compression and SE. We introduce an image adaptive VQ index compression algorithm suitable for SE, effectively combining remapping of indices, entropy, predictive, differential, and search order coding. We then present SE through codebook pseudorandom shuffling and block ciphering of the VQ index image bit-planes, index usage map, prediction information tables and full indices. Experimentally, the results demonstrate the improved performance and effectiveness of the proposed schemes.